Las lenguas de América Central y el idioma de sutiava según su documentación por Walter Lehmann - Künne, Martin (2015)
Between 1907 and 1909, the German linguist Walter Lehmann undertook an exploratory journey across several Central American countries. Under the auspices of the anthropological museums of Berlin, Hamburg and Munich, Lehmann, the scholar of Eduard Seler, investigated mainly archaeological, ethnographic, and historical sources. In addition, following his own areas of interest, Lehmann also collected vocabularies, phrases and short texts from 21 different indigenous groups. Based on this research, the young Berlin scientist wrote his dissertation about the Rama language (1914) and his postdoctoral thesis on the Sutiava tongue. Further linguistic data, collected during the same period of investigation, were published in the famous opus: The languages of Central America in their mutual relationships and connections to South America and Mexico in 1920. Although the edition was limited to 400 copies, the study is considered the most profound historical source of linguistic information about Central America to the present day. This article outlines the historical context, the scientific approach and the general structure of Lehmann’s opus. By describing the documentation of the Sutiava tongue, the author demonstrates the current system of documentation as well as the methodological limitations of the historical approach applied during the formation of American Studies.